PEMANTAUAN DAN EDUKASI KESEHATAN IBU HAMIL PASCA GEMPA DI DESA TAMPALANG KECAMATAN TAPPALANG KABUPATEN MAMUJU - Andi Hariati; Erniawati Erniawati; Rosmina Anisa; Annisa Fitri Mutmainna (JCS, 2021)
In 2021 Mamuju Regency, West Sulawesi Province was rocked by a large earthquake. Tampalang Village, Tappalang District, Mamuju Regency, is one village that was affected by the earthquake. This earthquake caused a lot of losses both physically and non-physically. Non-physical losses include trauma, especially to children and pregnant women. After the earthquake, some of the survivors were injured and needed health monitoring. The limited number of health personnel and the damage to health facilities have resulted in many earthquake victims who have not been handled evenly, including pregnant women. Residents live in refugee camps with limited sanitation and rainy season weather worsens the health conditions of the population, especially pregnant women, postpartum mothers, infants, and toddlers. The purpose of this service activity is to provide health services to pregnant women by conducting examinations. The method used in this service activity is through education and health checks for pregnant women. The result of this activity is that while carrying out health services for pregnant women who experience health problems or anxiety because of the earthquake that hit Mamuju Regency.